Calculation of the fourth-rank molecular hypermagnetizability of some small molecules - Pagola, G.I. (2004)
A computational scheme was developed for a fourth-rank hyprmagnetizability tensor denoted by Xαβγδ. It was shown that this instrinsic property of diamagnetic atoms and molecules was useful to rationalize their nonlinear response to intense magnetic field. The terms connected with the fourth power of the perturbing field which represent the fourth-rank hypermagnetizability of the H2, HF, H2O, NH3, and CH4 molecules were evaluated at the coupled Hartree-Fock level of accuracy. The Gaugeless basis sets of increasing size and flexibility that adopted two different coordinate systems to estimate the degree of convergence of theoretical tensor components was employed.